Bourdieus Field, Capital, and Habitus in Religion - Grusendorf, Stephen (Journal for the sociological integration of religion and society, 2016)
Over his lifetime Pierre Bourdieu developed a highly sophisticated scheme by which he sought to explain how power was developed, kept, and transferred within society. Among his many contributions to sociology, the concepts of field, capital, and habitus loom large over the landscape of his achievements. This work seeks to uncover the various ways in which these three concepts have been understood to relate to religion. First, a brief summary of each of Bourdieus concepts will be presented. Next, the literature related to each of Bourdieus three concepts will be reviewed and synthesized in order to offer an organized view of how the various approaches to each relates to religion specifically. It is the ultimate aim of this work to offer the reader and religious organizations a clearer understanding of how Bourdieus concepts of field, capital, and habitus shape their understanding of the various forms that religion takes within society. As will be demonstrated from the work of Bourdieu and others, religion can be understood as a place to belong within society, a promise of credit within society, or a lifestyle to adopt within society.